A population based study of unintentional firearm fatalities. Issue 1 (1st March 2001) - Cherry, D; Runyan, C; Butts, J
Abstract : Objectives —To describe the circumstances of fatal unintentional firearm injuries in a statewide population in a region of the United States with high firearm fatality rates and to compare to similar data from an earlier period in the same state. Methods —Analyses of North Carolina medical examiner database (1985–94) and review of medical examiner case reports (1990–94) and comparison to similar data from 1979–82. Results —A total of 390 unintentional shooting deaths occurred (0.59/100 000 population) between 1985–94 with the highest rate in the ages 15–24. Between 1990–94, handguns were responsible for 59% of these deaths compared to 40% in the 1979–82 period. Younger victims were more likely to be shot by family or friends, though, 53% of all deaths were self inflicted. In 45 cases, the person firing the weapon was reported to believe that the gun was unloaded or had the safety device activated. Conclusions —This study demonstrates changes in patterns of unintentional firearm fatalities in North Carolina in two decades, particularly the increase in incidence of events involving handguns. The results highlight the need for additional attention to efforts governing access to firearms, particularly handguns; technological advances in designing safer guns, and additional emphasis on safe storage policies and practices.